Pengaruh Kinerja Petugas Cleaning Service Terhadap Kepuasan Penumpang Ekonomi Kapal Motor Kelud PT. PELNI (Persero) - Irsyad Ardy Haryanto; Heni Pridia Rukmini Sari (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The purpose of this study was to determine the Effect of Cleaning Service Officers Performance on Passenger Economic Satisfaction MV. Kelud PT. PELNI (Persero). Data collection method to test the hypothesis using a questionnaire aimed at 90 respondents of sea transportation service users, especially economy passengers MV. Kelud PT. PELNI (Persero).T Test Results in this study have a calculated t value of 9,686. at the error level (alpha) 0.05 with the number of samples 90 and the number of independent variables 1, the value of t table is (1.987). Because the value of t arithmetic (9,686) is greater than t table (1,987) then H1 is accepted, meaning that there is an influence between Performance (X) on Customer Satisfaction (Y). The results of the calculation of the coefficient determination of the variable Influence the Performance of Cleaning Service Officers on Passenger Economic Satisfaction MV. Kelud PT. PELNI (Persero) is 51.6% It shows that the Performance of Cleaning Service Personnel variables has a positive and significant effect on the satisfaction of KM economic passengers MV. Kelud PT. PELNI (Persero) while the rest is influenced by other factors. As well as the recapitulation of the average score on the economic passenger satisfaction indicator is 4.06 (Good) which shows that in general, economy passengers of MV. Kelud PT. PELNI (Persero) is satisfied with the performance of the Cleaning Service Officers.